IMPLEMENTASI INTEGRASI AGAMA DAN SAINS: STUDI KASUS UIN MAULANA MALIK IBRAHIM MALANG - Suniati; Maksum; Asnawan; Muthi’atun Najiyah; Afifatus Sholihah; Abd. Hadi (PT. Saha Kreasi Indonesia, 2025)
The integration of religion and science is a scientific paradigm developed to overcome the dichotomy between Islamic sciences and general sciences in Islamic higher education. This study aims to examine in depth the implementation of religion and science integration at the State Islamic University (UIN) Maulana Malik Ibrahim Malang, one of the Islamic universities that institutionally promotes an integrative scientific paradigm. This research employs a qualitative approach using a case study method. Research data were obtained through documentation studies of the curriculum, the university’s vision and mission, academic guidelines, and various institutional policies related to the development of integrative knowledge. The findings show that the implementation of religion and science integration at UIN Maulana Malik Ibrahim Malang is realized through an integrative curriculum design, the strengthening of Islamic studies courses as the foundation of scientific development, and the establishment of a religious academic culture that encourages dialogue between revelation and reason. However, several challenges remain in practice, particularly differences in lecturers’ understanding of the integration concept and limitations in its implementation in classroom learning. This study is expected to contribute theoretically and practically to the development of integration models for religion and science in Islamic higher education institutions.